Corporate Sustainability and Environmental Certification in Companies (Research, Society and Development, 2022)
As environmental issues are, in a definitive way, inserted in the interests of society and organizations, being discussed looking for new alternatives, companies included in their scope the concern with the environmental impacts they generate on the environment in their list of guidelines. Sustainability in Brazilian organizations is a topic that is being increasingly addressed, dating back to the 20th century. The way for companies to publicly prove this respect for the environment is by acquiring environmental certification. In this article, we will approach ISO 14001 certifications through quantitative methodologies and bibliographic research, presenting the results of certifications obtained in the last six years by Brazilian companies, as well as the importance of these certifications not only for organizations but also for society as a whole. one all.